Firm Financing in Chile after the 2014-15 Tax Reform : Debt or Equity? - Hernandez T., Leonardo (World Bank, Washington, DC, 2016)
This paper analyzes the effects of the 2014-15 Chilean tax reform on firms' incentives to retain earnings and finance their operations with equity versus debt. The analysis comprises a comparison with the situation of the pre-reform period, and draws some conclusions about firms' valuation. The approach consists of analyzing the effects of the tax reform on total taxes paid and cash flows received by investors. Although the final effects are specific to the firm and investor, as they depend on the firm's dividend payout ratio and each investor's personal income tax rate, the results show that in general the reform reduced the value of firms and lessened the incentives to retain earnings. The simulations show that the majority of firms would choose the accrual or "attributed" tax–based system. However, if the latter is not permitted, firms will choose debt over equity. The cash-based or semi-integrated system becomes the preferred option only when elusion (or tax avoidance) is possible.